2018
DOI: 10.1099/jgv.0.001121
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic inactivation of Bovine herpesvirus type 1 (BoHV-1) by porphyrins

Abstract: In this work, the photodynamic efficiency of anionic meso-tetrakis sulfonophenyl (TPPS4), cationic meso-tetrakis methylpyridiniumyl (TMPyP) and their zinc complexes (ZnTPPS4 and ZnTMPyP) in the inactivation of Bovine herpesvirus type 1 (BoHV-1) was evaluated. At a non-cytotoxic concentration, all porphyrins showed significant antiviral activity after irradiation using a halogen lamp. The efficiency of the cationic porphyrins was higher than that of the anionic ones. Porphyrin complexation with zinc increases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Referring to the concentration range of porphyrin-type photosensitizer molecules used in the literature on photodynamic inactivation of viruses in the range of 0.1–25 μM, we chose a moderate concentration of PpIX: 7.8 μM (0.2 mg/mL SiO 2 –PpIX) for virus inactivation research. We studied the photodynamic inactivation against VSV and HSV-1 (Figure A,C, respectively) with 0.2 mg/mL SiO 2 –PpIX.…”
Section: Resultsmentioning
confidence: 99%
“…Referring to the concentration range of porphyrin-type photosensitizer molecules used in the literature on photodynamic inactivation of viruses in the range of 0.1–25 μM, we chose a moderate concentration of PpIX: 7.8 μM (0.2 mg/mL SiO 2 –PpIX) for virus inactivation research. We studied the photodynamic inactivation against VSV and HSV-1 (Figure A,C, respectively) with 0.2 mg/mL SiO 2 –PpIX.…”
Section: Resultsmentioning
confidence: 99%
“…Herpes virus infection has serious complications especially in immunocompromised patients, pregnant women and infants [117]. In the following work the authors studied photodynamic activity of cationic TMPyP and anionic TPPS 4 , as well as their zinc complexes (ZnTMPyP and ZnTPPS 4 ) in inactivating bovine herpes virus type 1 (BoHV-1) [118] In dark toxicity studies, none of the samples affected virus viability. However, when BoHV-1 samples were irradiated in the presence of porphyrins, the effectiveness of the studied photosensitizers decreased in the following order: ZnTMPyP > TMPyP > ZnTPPS4 > TPPS 4 .…”
Section: •−mentioning
confidence: 99%
“…215 Similarly, a comparative study of cationic and anionic PSs with bovine herpes virus (BoHV) type-1 indicated a higher activity for zinc(II) complexes. 217 In a concurrent approach, 5,10,15,20-tetrakis(4sulfonatophenyl)porphyrin has been loaded onto fullerene. This nanoparticle PS was effective in the PDI of HSV-1, the PS loaded on fullerene being more efficient than the free PS.…”
Section: Figure 10mentioning
confidence: 99%